DEVELOPMENT OF ORODISPERSIBLE TABLETS OF LORATADINE CONTAINING AN AMORPHOUS SOLID DISPERSION OF THE DRUG IN SOLUPLUS® USING DESIGN OF EXPERIMENTS - NAIR, HEMA A.; GADHIRAJU, GAAYATHRI; SUNNY, GUNDETI (International Journal of Pharmacy and Pharmaceutical Sciences, 2023)
Objective: The objective of the present work was to develop an orodispersible tablet of loratadine, an orally active, non-sedating anti-histaminic, belonging to BCS Class II. The drug was prepared as a solid dispersion using Soluplus® as carrier and formulated into an optimal tablet using Design of Experiments. Methods: Solid dispersions of loratadine with varying ratios of Soluplus® were prepared by solvent evaporation and subjected to solubility study in simulated salivary fluid. Selected composition was characterized by differential scanning calorimetry and X-ray diffraction and formulated into an orodispersible tablet by direct compression after addition of suitable excipients. DOE based on a full factorial design was used to optimize the product using a trial version of JMP software, so as to obtain a tablet with low friability, rapid disintegration and maximal drug dissolution within 5 min. The optimized tablet was prepared and evaluated for several attributes, including in vivo disintegration and palatability. Results: A solid dispersion prepared with a 1: 4 ratio of loratadine: Soluplus® was found to show a 130-fold increase in drug solubility in the simulated salivary fluid. X-ray diffraction revealed loratadine in amorphous form. The exercise using DOE for optimization of the orodispersible tablet formula served to balance the proportion of crospovidone as super disintegrant and PVP as dry binder and yielded a formulation with good mechanical strength, rapid in vitro disintegration (39 sec) and dissolution of 93.78% of the drug within 5 min. When evaluated in vivo, the tablets were found to disintegrate in about 60 secs and were reported to be palatable. Conclusion: A patient-friendly dosage form containing a highly soluble form of loratadine was prepared and could be of potential benefit in offering quick relief from allergic conditions.